2019
DOI: 10.1007/s10120-019-00992-2
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural network for the diagnosis of early gastric cancer based on magnifying narrow band imaging

Abstract: Background Magnifying endoscopy with narrow band imaging (M-NBI) has been applied to examine early gastric cancer by observing microvascular architecture and microsurface structure of gastric mucosal lesions. However, the diagnostic efficacy of non-experts in differentiating early gastric cancer from non-cancerous lesions by M-NBI remained far from satisfactory. In this study, we developed a new system based on convolutional neural network (CNN) to analyze gastric mucosal lesions observed by M-NBI. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 35 publications
2
121
0
1
Order By: Relevance
“…[13][14][15][16][17][18][19] Recently, a few reports have assessed the usefulness of computer-aided diagnosis (CAD) systems for ME-NBI diagnosis of EGC using AI. 20,21 These results are almost equivalent to or slightly lower than the previously reported diagnostic accuracies of ME-NBI (90.4% 6 and 96.1% 7 ) performed by endoscopists in Japan. Moreover, although maximal magnification was stated as the method used in these two articles, the water immersion technique was not used.…”
Section: Introductionsupporting
confidence: 67%
“…[13][14][15][16][17][18][19] Recently, a few reports have assessed the usefulness of computer-aided diagnosis (CAD) systems for ME-NBI diagnosis of EGC using AI. 20,21 These results are almost equivalent to or slightly lower than the previously reported diagnostic accuracies of ME-NBI (90.4% 6 and 96.1% 7 ) performed by endoscopists in Japan. Moreover, although maximal magnification was stated as the method used in these two articles, the water immersion technique was not used.…”
Section: Introductionsupporting
confidence: 67%
“…All 4245 studies were screened and 106 full-length articles and/or abstracts were assessed. Nineteen studies 2 5 6 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 reported on the detection and/ or classification of gastrointestinal neoplastic lesions by CNN. Among the 19 studies, five 6 12 15 17 26 reported on efficacy of CNN in diagnosing esophageal neoplasia, eight 5 14 16 18 19 22 23 25 reported on use of CNN in neoplasia of the stomach and six 2 11 13 20 21 24 evaluated use of CNN in diagnosing colorectal neoplasia.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies 2 5 6 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 reported on the detection and/ or classification of gastrointestinal neoplastic lesions by CNN. Among the 19 studies, five 6 12 15 17 26 reported on efficacy of CNN in diagnosing esophageal neoplasia, eight 5 14 16 18 19 22 23 25 reported on use of CNN in neoplasia of the stomach and six 2 11 13 20 21 24 evaluated use of CNN in diagnosing colorectal neoplasia. Seven studies 5 11 12 14 19 20 25 used standard WLE, eight used NBI (magnifying and/ or non-magnifying) 2 6 13 15 18 22 23 26 and four 16 17 21 24 used a combination of standard WLE and/or NBI and/or chromo-endoscopy images ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have compared clinicians and AI with image interpretation or diagnostic performance on, for example, CT or gastroscopic images, and have shown that ML models are equivalent to or superior to specialists. [35,36] However, it is difficult to find a study that compares the predictive performance of clinicians and AI as in this study. Although it is an unfamiliar task for surgeons to predict the post-procedural outcome by looking only at tabulated letters and numerals, the surgeons' predictions were, surprisingly, not inadequate.…”
Section: Comparison Of Clinician and Ai Performancementioning
confidence: 97%